PENGEMBANGAN MEDIA AJAR BERBASIS AUDIO VISUAL (ANALISA PENGGUNAAN TRANSMITTER BAGI JAMA’AH HAJI KABUPATEN NGAWI) - Faridah, Anik (Institut Agama Islam Ngawi, 2024)
This research aims to develop audio-visual based teaching media using transmitters to support Hajj education in Ngawi Regency. This research was carried out using a development research method involving Ngawi Regency Hajj pilgrims as research subjects. This research was carried out in stages of developing teaching media, namely needs analysis, design, development and evaluation. The research results show that the use of audio-visual based teaching media using transmitters can increase the understanding of Hajj pilgrims in carrying out the Hajj pilgrimage. This research makes an important contribution to the development of Hajj education in Ngawi Regency. In the context of Hajj education, the use of audio-visual technology can be an effective means of supporting the understanding, preparation and experience of Hajj pilgrims. Through the development of audio-visual based teaching media using transmitters, Hajj pilgrims can obtain better information and knowledge regarding the implementation of the Hajj pilgrimage. This research also provides important implications for the development of learning methods that are more adaptive, effective and oriented towards the needs of Hajj pilgrims. In the context of religious and religious education, the use of audio-visual technology can be an effective means of improving the quality of learning. In conclusion, this research shows that the development of audio-visual based teaching media using transmitters can increase the understanding of Hajj pilgrims in carrying out the Hajj pilgrimage. The use of audio-visual technology can be an effective means of supporting religious and religious education. Therefore, the development of audio-visual based teaching media using transmitters can be used as a model for developing more innovative and effective learning methods in supporting religious and religious education.